Maternal and neonatal outcomes in twin and triplet gestations in Western Saudi Arabia - AlBasri, Samera F. (Saudi Med J, 2017)
OBJECTIVES: Tocompare maternal and neonatal complications in twin and triplet gestations at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. METHODS: Retrospective medical records of 165 women with 144 twin and 21 triplet pregnancies from 2004 to 2011 were analyzed. Comparisons were carried out for maternal complications, gestational age at birth, neonatal birth weight, and neonatal intensive care admission. RESULTS: Most common complications were preterm birth (49%), gestational diabetes mellitus (13.3%), and premature rupture of membrane (4.8%). All triplet pregnancies and 42% twin pregnancies terminated in preterm birth. Gestational length was longer (p<0.001) in twin births (36.0 ± 3.05 weeks) than for triplet births (32 ± 3.81 weeks). Rates for in vitro fertilization, ovulation induction, and cesareans were higher in women with triplets than in those with twins. Neonatal intensive care unit (NICU) admission was higher (p<0.001) for triplets (76.2%) than for twins (23.6%). The mean weight of twins was 2333.83 ± 558.69 grams and triplets was 1553.41 ± 569.73 grams. Hyaline membrane disease, neonatal jaundice, and neonatal sepsis were most common neonatal complications. CONCLUSION: Neonates from triplet pregnancies were preterm, had low birth weight and needed more often NICU admission in comparison to those from twin pregnancies.